Experimental Diagnostics and Investigations on Cavitation in Engine Injector Nozzles - Wensing, Michael; Rieß, Sebastian; Mamaikin, Dmitrii; Conrad, Chris; Neubauer, Alexander (Cavitation and Bubble Dynamics – Fundamentals and Applications, 2021)
Cavitation may appear in various hydraulic components, such as injectors, pumps, and valves. These components are used in various technical fields, such as industrial hydraulic systems or automotive systems (steering, braking, and injection systems). The phenomena of cavitation play an important role in the performance of modern fuel injectors. Researchers in both academia and industry have intensively studied this field of hydrodynamics in recent decades. Such a strong interest is due to the appearance of cavitation inside fuel injector nozzles, which influences the spray characteristics and overall function of the injectors. Generally, the phenomena of cavitation can be investigated experimentally as well as numerically. The chapter focuses on techniques and examples for experimental investigations<br
CRIS-Team Scopus Importer:2024-12-16
Keywords: Diesel; Experiments; Gasoline; Injection; Nozzle; Optical nozzle; Optics